9514 1404 393
Answer:
(x^(1/2))^2 = x^(2/2) = x
Explanation:
The square root of a number, when multiplied by itself, gives the original number.
(√x)(√x) = x
The rule for exponents is that powers of the same base, when multiplied, will be the base to the sum of those powers.
(a^b)(a^c) = a^(b+c)
Also, the first power of a number is that number itself.
__
![x^{(1)/(2)}* x^{(1)/(2)}=x^{(1)/(2)+(1)/(2)}=x^1=x\\\\ \text{Compare to ...}\\\\ √(x)*√(x)=x](https://img.qammunity.org/2022/formulas/mathematics/college/hbjtd1qcry3mt587t80gszgv9xgplxs253.png)